Political Disenfranchisement as a Means of Combating Corruption - Suwito, Suwito; Meliana, Yang; Haikal, Jenggis Khan; Riyanto, Ontran Sumantri; Yassine, Chami (LPPM Universitas Trunojoyo Madura, 2024)
The purpose of this study was to explore effective ways of determining the duration of political disenfranchisement of corruption convicts in Indonesia, with the aim that this punishment serves as an effective deterrent effect without violating human rights. The study also aims to analyze the long-term impact of political disenfranchisement of corruption convicts on democratic processes and their reintegration into post-detention society. This research is categorized as normative legal research and uses a philosophical and analytical approach that focuses on rational, critical analytical, and philosophical views on applicable legislation and legal theory. The research utilizes analytical descriptive methods to examine positive law enforcement practices related to these issues. Based on the severity of corruption cases and the rehabilitation potential of convicts, determining the duration of political disenfranchisement is crucial. Fair review and appeal mechanisms should be in place to support the social and political reintegration of ex-convicts. The study also emphasizes the importance of political disenfranchisement as part of a broader legal system to support healthy democracy, transparent governance, and inclusive societies.